Epithelial-Stromal Polyps of the Colon Are Not Perineuriomas. Issue 1 (14th December 2020) - Hissong, Erika; Yantiss, Rhonda K
Abstract: Objectives: Some colorectal polyps contain serrated or tubular crypts surrounded by whorls of spindle cells that expand the mucosa. These epithelial-stromal polyps have been termed benign fibroblastic polyps or, more commonly, perineuriomas . We hypothesized that these lesions are pathogenetically heterogeneous polyps that share in common exuberant fibroblastic proliferations derived from the pericryptal sheath. Methods: Forty-six epithelial-stromal polyps containing serrated crypts (n = 21) and nonserrated crypts (n = 25) were evaluated with epithelial membrane antigen and BRAF V600E immunohistochemical stains, and a subset was subjected to next-generation sequencing for BRAF mutations. Polyp morphology and immunohistochemical results were correlated with clinical information. Results: Epithelial-stromal polyps containing serrated crypts were significantly associated with other sessile serrated polyps (43%, P = .01) and hyperplastic polyps (29%, P = .006). They also showed BRAF V600E abnormalities (95%) and strong, patchy epithelial membrane antigen staining of spindle cells (95%). In contrast, polyps with nonserrated crypts lacked BRAF alterations and infrequently showed robust EMA staining of stromal cells (16%, P < .01). Conclusions: Benign epithelial-stromal polyps with serrated epithelium are biologically similar to sessile serrated polyps and should be classified as such to ensure appropriate clinical surveillance. The nature of polyps without serrated crypts is less clear, but evidence that they are perineuriomas is circumstantial at best.